The Influence of Price and Promotion on Purchase Decision and Its Impact on Telkomsel Prepaid Card Consumer Satisfaction (In Kebon Manggis Urban Village) - Maftuchach, Viniyati (International Journal of Psychosocial Rehabilitation, 2020)
This study was conducted to determine the effect of price and promotion on purchasing decisions and their impact on consumer satisfaction of Telkomsel prepaid card. In this study there are four variables studied namely price, promotion, purchasing decisions and customer satisfaction. Samples obtained as many as 100 respondents and taken by Purposive Sampling is a technique to determine the sample of research with some specific considerations that aims for data obtained later can be more representative. The number of samples in this study is determined by the method of Structural Equation Modeling (SEM) Hair et al, 2011. The data analysis used is SmartPLS version 3. 2. 3. The results showed that all hypothesis acceptable except on variable which have negative influence and not signifikan between promotion to consumer satisfaction because have coefesien value of parameter-0,036, t-statistic 0,374 and P value 0,708 which means promotion to satisfaction not accepted